An experimental investigation of leakage flow paths in soil surrounding leaks in water distribution systems - Teeluckdharry, Sahil (Water Research Group, 2017)
Over the last few decades, water stress has been imminent in most municipalities around the world. The problem of water losses from pipelines is a major concern due to the increasing demands. Leakage is normally responsible for a large percentage of water losses in distribution systems and results in enormous wastage of valuable resources and energy. Leaks may be developed in many forms and locations in the system and active leak detections are required to find and repair damaged pipes. Few studies have been done on the soil-leak interaction in real pipeline systems. Recent research have shown that the high velocity water jets entering the surrounding soil causes a fluidisation zone outside leaks. The fluidised zone of soil and water is responsible for dissipating most of the energy of the water jet from the pipe leak and thus, limiting the leak's ability to reach soil surface. In municipalities where active leak detections are not implemented, it is easier for municipalities to detect leaks if they appear on the surface and thus, it is crucial to understand the routes of water leaks and the factors causing them to appear above the ground. This study investigated the soil-leak interaction focusing mainly on factors affecting leakage flow paths in water distribution systems. An experimental set up was designed and built to study the different factors in a controlled environment. A series of experiments were performed where water jets from manufactured circular leaks were released in different trench set ups. Three main variables were investigated namely flow rate, leak orientation and in-situ soil to start understanding the movement of the leak flow as a preliminary study. The volumetric moisture content were measured using EC-5 moisture sensors at different locations in the tank to analyse the movement of leakage water and iPERLS smart water meters were used to measure the flow of water through the walls of the trench. The results of the experiments showed how much leakage water is actually lost through the side and bottom walls. The volumetric moisture content readings indicated the movement of the leak in the tank. The results of the study indicated that leak orientation has the greatest influence on the paths of the leaks. Also, the flow rate had to be increased to a very high value so that the leak appears above the sand surface. The permeability of the in-situ soil was found to have the least effect on the leakage flow paths.